2009
DOI: 10.1038/onc.2009.112
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc activates multiple metabolic networks to generate substrates for cell-cycle entry

Abstract: Cell proliferation requires the coordinated activity of cytosolic and mitochondrial metabolic pathways to provide ATP and building blocks for DNA, RNA and protein synthesis. Many metabolic pathway genes are targets of the c-myc oncogene and cell-cycle regulator. However, the contribution of c-Myc to the activation of cytosolic and mitochondrial metabolic networks during cell-cycle entry is unknown. Here, we report the metabolic fates of [U-13 C] glucose in serum-stimulated myc À/À and myc þ / þ fibroblasts by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 22 publications
4
127
0
7
Order By: Relevance
“…In addition to the Akt/mTOR pathway (6,12), it is essential that cells up-regulate gene expression to allow mitochondria to use glucose as a metabolic fuel to support ATP generation and biosynthesis. Although the transcription factors Myc and HIF1α may play key roles to up-regulate expression of glycolytic genes (14,28,29), our data suggest that ERRα broadly impacts T-cell metabolism and is particularly critical in T cells to reprogram mitochondria to use glucose as an anabolic source (Fig. S10D).…”
Section: Resultsmentioning
confidence: 89%
“…In addition to the Akt/mTOR pathway (6,12), it is essential that cells up-regulate gene expression to allow mitochondria to use glucose as a metabolic fuel to support ATP generation and biosynthesis. Although the transcription factors Myc and HIF1α may play key roles to up-regulate expression of glycolytic genes (14,28,29), our data suggest that ERRα broadly impacts T-cell metabolism and is particularly critical in T cells to reprogram mitochondria to use glucose as an anabolic source (Fig. S10D).…”
Section: Resultsmentioning
confidence: 89%
“…In prostate-cancer cells, AR has been shown to regulate metabolic genes involved in glycolysis, PPP, fatty acid, and nucleotide synthesis (11). On the other hand, as one of the most highly amplified oncogenes in many cancers (23), c-Myc emerges as a master regulator of global metabolism, including those regulated by AR, as well as glutamine metabolism and the TCA cycle (14,15). We showed, in both cases, that PCGEM1 associated with the transcription factors, enhanced their transactivation activities, enriched their recruitments to the target promoters, and up-regulated the target genes in all of the pathways described above.…”
Section: Discussionmentioning
confidence: 99%
“…2; summarized in Fig. S3) (14,15). Second, chromatin isolation by RNA purification (ChIRP) analysis showed that PCGEM1 physically associated to a subset of the metabolic gene promoters (Fig.…”
Section: Pcgem1mentioning
confidence: 99%
“…In Burkitt's lymphoma, for example, the c-Myc gene is translocated to one of the Ig loci in virtually all tumors (5,7,8). The MYC oncogene contributes to tumorigenesis by functioning as a global regulator of transcription involving many cellular programs, including cellular growth, metabolism, and lipid synthesis (9,10). MYC induces a global shift in metabolism associated with anaerobic glycolysis, a phenomenon known as the Warburg effect (11).…”
mentioning
confidence: 99%